2013
DOI: 10.1111/aos.12062
|View full text |Cite
|
Sign up to set email alerts
|

Acute–onset diplopia

Abstract: . Purpose:  To investigate the clinical features of all patients with acute–onset diplopia presenting to the ophthalmology department. Methods:  The notes of every patient who presented with acute onset (<4‐week duration) diplopia to the ophthalmology clinic over a 2‐year period were reviewed. Data regarding clinical features, underlying aetiology, past medical history, investigations and outcomes were extracted. Results:  One hundred and forty‐nine patients presented with 53.7% having an isolated third, fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 7 publications
4
14
0
1
Order By: Relevance
“…The most common cause of binocular diplopia is isolated cranial nerve palsies (40-67%). [3][4][5] In our study we found cranial nerve palsies in 51.4% of our patients, of these 31.4 % were sixth nerve palsy, 11.4% third nerve palsy and 8.6% fourth nerve palsy. Merino et al similarly found the most frequent cause, as cranial nerve palsies and in their study, sixth nerve palsy was the most frequent.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The most common cause of binocular diplopia is isolated cranial nerve palsies (40-67%). [3][4][5] In our study we found cranial nerve palsies in 51.4% of our patients, of these 31.4 % were sixth nerve palsy, 11.4% third nerve palsy and 8.6% fourth nerve palsy. Merino et al similarly found the most frequent cause, as cranial nerve palsies and in their study, sixth nerve palsy was the most frequent.…”
Section: Discussionsupporting
confidence: 57%
“…6 The frequency of isolated nerve palsies was 53.7% in the study of O'Colmain and of these, 25.5% were sixth nerve palsies, 16.1% fourth nerve palsies and 12.1% third nerve palsies. 5 In early childhood, in the presence of acute esotropia, patients usually do not suffer from diplopia because of suppression. However, if acute esotropia develops in older ages, patients usually complain of diplopia.…”
Section: Discussionmentioning
confidence: 99%
“…26 Genel olarak, ileri yaşta akut başlan-gıçlı, pupiller tutulumun olmadığı hastalarda eşlik edebilen sistemik risk faktörlerinin araştırılması, görüntüleme yöntemlerinden ziyade etiyolojik araştırmada ilk tercih olmalıdır. 27 Üç ay içerisinde düzelmeyen ve vasküler patolojiye bağlı olduğu düşünülen hastalarda, özellikle anizokorinin >2 mm olduğu akut başlangıçlı hastalarda veya travma öyküsü olmayan genç hasta grubunda altta yatan sebebin ortaya çıkartılması için MRG'nin gerekliliği unutulmamalıdır. 18,[28][29][30][31][32][33] Bizim çalışmamızda, literatüre paralel olarak, 4. kraniyal sinir felci daha az oranda (%15,3) saptanmıştır.…”
Section: Discussionunclassified
“…3 In these cases, a lesion is usually not found even by the current neuroimaging techniques. Although a brain tumour needs to be ruled out in cases of chronic abducens nerve palsy, abducens nerve palsy caused by a brain tumour is mostly accompanied by other cranial nerve palsies.…”
Section: Introductionmentioning
confidence: 99%